Study on conditions of hydrolysis green seaweed Chaetomorpha limum by enzyme and application of inbioethanol production - Trung, Vo Thanh; Hau, Le Nhu; Hang, Nguyen Thanh (Academia Journal of Biology, 2016)
Chaetomorpha linum seaweed composes a high carbohydrate content, various types of polysaccharides, with 38% cellulose in material. In our paper, the material from Ch. linum was treated by enzyme L Visocozyme and we found optimized hydrolysis conditions, vis. enzyme concentration: 0.85 ml/g (42.5 IU/g), time: 33 hours, temperature: 50oC, and pH: 5.2. The hydrolysis results of Ch. linum were: 50.3 g/l sugar solution which were fermented with Red Ethanol yeast under the following conditions pH: 4.5, temperature: 27oC, rotation rates; 50 rpm, CFU yeast: 109/l, and fermentation time: 108 hours. Ethanol product of fermentation process was 14.4 g/l.